2009
DOI: 10.1007/s00213-009-1688-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neuropsychological effects of ecstasy in middle-aged ecstasy/polydrug users

Abstract: Rationale Studies reporting ecstasy-induced serotonintoxicity and (neuro)psychological dysfunctions have been conducted in young adults. Little is known about ecstasy effects later in life, when serotonin levels and cognition decrease as a consequence of normal ageing. Objective This study aimed to assess whether harmful effects of ecstasy only add to or also interact with agerelated neuropsychological decline. Methods Attention, verbal and visual memory, visuospatial ability, self-reported depression, sensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 38 publications
1
9
1
Order By: Relevance
“…Our largely negative findings appear inconsistent with many past studies as well as some more recent investigations [55–57] that report lowered cognitive functions in ecstasy users. Indeed, our findings are inconsistent with several findings in our own pilot study [15], possibly because heavy users in the earlier study were tested after briefer median abstinence (59.5 versus 121 days), possibly because of differences in unmeasured confounders or possibly because of chance alone.…”
Section: Discussioncontrasting
confidence: 99%
“…Our largely negative findings appear inconsistent with many past studies as well as some more recent investigations [55–57] that report lowered cognitive functions in ecstasy users. Indeed, our findings are inconsistent with several findings in our own pilot study [15], possibly because heavy users in the earlier study were tested after briefer median abstinence (59.5 versus 121 days), possibly because of differences in unmeasured confounders or possibly because of chance alone.…”
Section: Discussioncontrasting
confidence: 99%
“…Research into the effects of Ecstasy has focused on the young and relatively little is known about the effects in middle-aged and older adults. What evidence there is suggests that middle-aged Ecstasy/polydrug users show the same type of deficits on cognitive testing as younger adults (Schilt et al 2010) but the question as to whether the effects of Ecstasy and ageing interact has not yet been adequately addressed.…”
Section: Discussionmentioning
confidence: 98%
“…Data for meta‐analysis were obtained from 12 of the 22 studies identified in Table as using tasks in this category. With regard to the 10 studies excluded from the meta‐analysis, two had included control participants with minimal ecstasy exposure (Schilt et al ., , ). As minimal exposure to ecstasy has been associated with some effects on cognitive performance (Schilt et al ., ), it was decided that it was safer to omit these two studies from the analysis.…”
Section: Resultsmentioning
confidence: 99%